Indonesia’s Economic Diplomacy to South Korea in Increasing Coffee Exports in 2016 – 2021 - Pertiwi, Dian; Darmastuti, Shanti; Yudhono, Raden Maisa (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
As a coffee-producing country, Indonesia needs help exporting its coffee to South Korea, which has high coffee consumption. It causes the value and volume of Indonesian coffee exports to fall below expectations. This research aims to discuss the export of Indonesian coffee to South Korea by using international trade theory and the concept of economic diplomacy. This study uses descriptive qualitative methods with primary data from semi-structured interviews, while secondary data is obtained from documents and literature related to data collection collected from January – April 2023. The results of this study are economic diplomacy carried out to maximize Indonesian coffee exports in 2016 – 2021, consisting of business matching, coffeeversation, the Seoul coffee expo and Seoul café show, and the role of government and private actors. These efforts significantly increased the value and volume of Indonesian coffee exports to South Korea the following year.